استخدام لعبة تخمين الكلمة والحركة لترقية تعليم مهارة الكلام لطالبات المعهد السلفي الفطرة سورابايا - Finaturrohmatika Finaturrohmatika; Mu’at Mu’at (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
In learning Arabic, the ability to speak is often a challenge for many students due to limitations in vocabulary acquisition, understanding of grammar, and confidence to speak the language. This study aims to determine the effectiveness of charades and style games in improving the maharah kalam skills of Assalafi Al Fithrah Surabaya Islamic boarding school students. This game learning of guessing words and styles is applied in the ulya PI language room where members consist of different levels and language abilities. So that this game, has disadvantages, namely because of the different levels of maharah kalam, but this game also makes language learning more active and fun and the students of the language room are more confident in conveying something that is contained in the thoughts and ideas that arise, and this game can add new vocabulary. The objectives of this research are: (1) the use of the word and movement guessing game to promote the teaching of speech skill for female students of the Salafi institute (2) the motivating and inhibiting factors in using the word and movement guessing game to promote the teaching of speech skill for female students of the Salafi institute. The researcher used a qualitative qualitative approach, meaning a descriptive analytical method. The method of collecting data by direct observation, interview, and documentation. The results of the research from the researcher's presentation are: (1) Overcoming the challenge of teaching speech skill in the upper language class for female students due to the diversity of students' abilities and the assumption of Arabic language difficulty through the effective and fun way of the word and movement guessing game. The observations showed an increase in speech skill after applying this method, which aims to increase vocabulary, sentence formation and practice.